A H2O2‐Supplied Supramolecular Material for Post‐irradiated Infected Wound Treatment. Issue 9 (29th January 2023) - Du, Peidong; Shen, Yanzhe; Zhang, Baoli; Li, Shan; Gao, Minzheng; Wang, Ting; Ding, Xiaokang; Yu, Bingran; Wang, Zhen‐Gang; Xu, Fu‐Jian
Abstract: Photodynamic therapy (PDT) is a light triggered therapy by producing reactive oxygen species (ROS), but traditional PDT may suffer from the real‐time illumination that reduces the compliance of treatment and cause phototoxicity. A supramolecular photoactive G‐quartet based material is reported, which is self‐assembled from guanosine (G) and 4‐formylphenylboronic acid/1, 8‐diaminooctane, with incorporation of riboflavin as a photocatalyst to the G4 nanowire, for post‐irradiation photodynamic antibacterial therapy. The G4‐materials, which exhibit hydrogel‐like properties, provide a scaffold for loading riboflavin, and the reductant guanosine for the riboflavin for phototriggered production of the therapeutic H2 O2 . The photocatalytic activity shows great tolerance against room temperature storage and heating/cooling treatments. The riboflavin‐loaded G4 hydrogels, after photo‐irradiation, are capable of killing gram‐positive bacteria (e.g., Staphylococcus aureus ), gram‐negative bacteria (e.g., Escherichia coli ), and multidrug resistant bacteria (methicillin‐resistant Staphylococcus aureus ) with sterilization ratio over 99.999%. The post‐irradiated hydrogels also exhibit great antibacterial activity in the infected wound of the rats, revealing the potential of this novel concept in the light therapy. Abstract : A post‐irradiation photodynamic therapy is presented that has no requirement for confinement of the patients to the illumination source. Supramolecular riboflavin‐loaded G4‐hydrogels are triggered by blue light to catalytically generate H2 O2, which is then subjected to the infected wound for killing bacteria.